Kaidah Memahami Kisah Dalam Al-Quran Perspektif Mutawali al-Syarawi - Nafisatun Nuri; Fakhrijal Ali Azhar; Ahmad Musyafiq (MAGHZA, 2020)
The study of the Koran's stories focused on the excavation of its historical aspect. This was done to prove the existence of such narratives in the Koran as historical facts that happened. On the other hand, it is often the precautionary care of the story, even to be neglected. Mutawalli al-Sya'rawi came by offering insight into the story in the Koran, not only by digging out its heart, but also creating a similar story in every place and time. The study USES a descriptive approach. The things accredited by al-Sya'rawi is written in the code that doesn't give the character's real name, and that story will be repeated everywhere and every time. Like pharaoh that zalim, dictator, and raised himself. So did the dzulqarnain, who is good and empowering the weak. The personages of these two characters will continue to exist in life, wherever and wherever.